Origins of the Banda Arcs Collisional Orogen and the Banda Sea - Satyana, Awang Harun (Berita Sedimentologi, 2012)
Many of the best examples of young arc-continent collision are found in eastern Indonesia, where the northern margin of Australia has been in collision throughout the Neogene with a succession of island arc systems. The Banda Arc is the youngest of these collision zones and forms the present plate boundary in this region. Behind the Banda Arcs, is the Banda Sea oceanic crust with its debatable origin.